Transcriptomic Profiling Reveals Key Genes Underlying Cold Stress Responses in Camphora - Shi, Bowen; Zheng, Linlin; Wang, Yifeng; Wang, Qirui (Life (Basel, Switzerland), 2025)
The genus Camphora encompasses species of significant ecological and economic importance, such as C. parthenoxylon and C. officinarum, which exhibit distinct phenotypic traits and stress responses. This study seeks to elucidate the molecular basis of cold tolerance through comparative transcriptomic analysis complemented by physiological characterization. RNA sequencing revealed 6123 differentially expressed genes between the two species, with enriched pathways related to cold stress, oxidative stress, carotenoid biosynthesis, and photosynthesis. Key genes, such as annexin D5, chlorophyll a/b-binding protein, early light-induced protein 1, 9-cis-epoxycarotenoid dioxygenase, were identified as critical regulators of frost resistance, photosynthetic efficiency, and carotenoid biosynthesis. Functional enrichment analyses highlighted the involvement of signal transduction, membrane stabilization, and secondary metabolism in adaptive responses. Physiological assays supported these findings, showing higher chlorophyll and carotenoid content and enhanced antioxidative enzyme activities in C. parthenoxylon. These results provide valuable insights into the genetic and biochemical mechanisms underlying stress adaptation in Camphora species and offer promising targets for enhancing resilience in economically valuable plants.